Long noncoding RNAs responsive to Fusarium oxysporum infection in Arabidopsis thaliana. Issue 2 (7th October 2013) - Zhu, Qian‐Hao; Stephen, Stuart; Taylor, Jennifer; Helliwell, Chris A.; Wang, Ming‐Bo
Summary: Short noncoding RNAs have been demonstrated to play important roles in regulation of gene expression and stress responses, but the repertoire and functions of long noncoding RNAs (lncRNAs) remain largely unexplored, particularly in plants. To explore the role of lncRNAs in disease resistance, we used a strand‐specific RNA‐sequencing approach to identify lncRNAs responsive to Fusarium oxysporum infection in Arabidopsis thaliana . Antisense transcription was found in c . 20% of the annotated A. thaliana genes. Several noncoding natural antisense transcripts responsive to F. oxysporum infection were found in genes implicated in disease defense. While the majority of the novel transcriptionally active regions (TARs) were adjacent to annotated genes and could be an extension of the annotated transcripts, 159 novel intergenic TARs, including 20 F. oxysporum ‐responsive lncTARs, were identified. Ten F. oxysporum ‐induced lncTARs were functionally characterized using T‐DNA insertion or RNA‐interference knockdown lines, and five were demonstrated to be related to disease development. Promoter analysis suggests that some of the F. oxysporum ‐induced lncTARs are direct targets of transcription factor(s) responsive to pathogen attack. Our results demonstrated that strand‐specific RNA sequencing is a powerful tool for uncovering hidden levels of transcriptome and that IncRNAs are important components of the antifungal networks in A. thaliana .